An Amperometric Biosensor Based on Alanine Dehydrogenase for the Determination of Low Level of Ammonium Ion in Water - Ling, TL; Ahmad, M; Heng, LY (Hindawi Publishing Corporation, 2024)
Indexed by WOS/ Scopus